Changes in peripheral blood test results among adults in the six years following the Great East Japan Earthquake: the Fukushima Health Management Survey - Hosoya, Mitsuaki; Hayashi, Fumikazu; Satoh, Hiroaki; Okazaki, Kanako; Sato, Shiho; Hashimoto, Koichi; Sakai, Akira; Ohira, Tetsuya; Ishikawa, Tetsuo; Kazama, Junichiro J.; Watanabe, Kazuyuki; Nagao, Masanori; et al. (FUKUSHIMA JOURNAL OF MEDICAL SCIENCE, 2025)
The Fukushima Health Management Survey, conducted by Fukushima Prefecture since the 2011 Great East Japan Earthquake (GEJE), has not identified any health effects from radiation exposure.　Complete blood counts (CBC), which are sensitive to radiation exposure, have not shown lymphocytopenia, neutropenia, anemia, or thrombocytopenia, but the white blood cell fractions have not yet been analyzed since 2011.　We classified 25,885 residents (11,383 male, 14,502 female;age range, 16-84 years) in evacuation areas with external exposure dose estimates based on behavioral surveys conducted 4 months after the GEJE into two groups (0-1 [≥0 and <1] and ≥1 mSv) and analyzed changes in CBC and leukocyte fractions from fiscal year (FY) 2011 to FY2017 and their influencing factors.　Compared with FY2011, no significant increase in the number of residents with leukopenia was seen, but the rate of male residents with anemia increased through 2017, regardless of the radiation exposure dose, but factors contributing to the development of anemia were more critical in males.　No links were found between the development of anemia and smoking, evacuation, or heavy alcohol drinking, whereas significant associations were found with thinness and older age.　These findings suggest that malnutrition is a cause of anemia, especially in males.